Concepts for the IT infrastructure at a university of applied sciences using the example of data management in the EU project DIVAGRI: Interdisciplinary tasks of business informatics in the areas data management, data quality management and service-oriented IT - Rüdiger Steffan; Thomas Kästner; Roland Hinz; Julia Matela; Paul Facklam; Lothar Vigelahn; Sebastien Clerc-Renaud (Hochschule Wismar, Fakultät für Wirtschaftswissenschaften, 2024)
Virtualization is indispensable for a service-oriented IT infrastructure, and hybrid models are also obvious in research and teaching in order to use cloud environments and on-premises solutions equally. In addition to multi-cloud solutions, internal integration concepts are also important if an organization advantageously operates multiple server infrastructures. The strategies for this are summarized in this article. The internationally oriented EU project DIVAGRI at Wismar University of Applied Sciences serves as a case study, in which innovative bio-based solutions for agricultural production in sub-Saharan Africa are implemented and tested. The IT management and business information systems of the Business Faculty are involved in the area of data management. In particular, the processes and experiences in the gradual provision and agile development of a headless CMS and a farmer app are described and discussed, and perspectives for ensuring data quality, monitoring and reporting are shown.
Keywords: Q16; C81; 330; agricultural; DevOp; diversification; headless CMS; virtualization